Experimental investigation on bond-slip behavior of epoxy-coated rebars in steel fiber reinforced concrete - Shicheng Zheng; Yixuan Li; Qian Feng; Xu Liang; Xinhang Wu; Rongqiao Xu (Case Studies in Construction Materials)
Epoxy-coated rebars (ECRs), as a cost-efficient solution to combat corrosion, suffer from severe low bond strength in concrete. Aiming at balancing the low bond strength and high corrosion-resistance ability of ECR, steel fiber reinforced concrete (SFRC) has been taken as a possible solution by many researchers, as it shows enhanced corrosion resistance with minimal expansion or cracking. To further explore the possibilities of this solution, this paper conducts experimental investigation to examine the bond-slip behavior between SFRC and ECR. Different concrete types, rebar types, and rebar diameters are taken into consideration in the analysis of 27 specimens. The failure modes are classified and the assessment of critical factors is performed based on the collected bond-slip curve. CT scanning is conducted to further reveal the mechanism of failure. Furthermore, the debonding strength and crack spacing were discussed to establish a robust basis for the subsequent calculation of the load-bearing capacity of ECR-reinforced SFRC structures.